2018
DOI: 10.18632/aging.101534
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-146b inhibits autophagy in prostate cancer by targeting the PTEN/Akt/mTOR signaling pathway

Abstract: Prostate cancer (PCa) is considered as a common visceral cancer in males and the sixth major cause of cancer-related deaths in males worldwide. Significant diagnostic and therapeutic advances have been made in the past decades. However, an improved understanding of their molecular mechanism is still needed. In the present research, we first detected the expression of miR-146b by quantitative real-time PCR (qRT-PCR) and found that miR-146b expression was increased in PCa. Subsequently, we found that miR-146b pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The decline in Pink1 expression was also observed in the nuclei and cytoplasm of the RGC layer of aging retinas [42] (Figure 4F). Microtubule-associated protein 1B light chain 3B (LC3B) is a marker of autophagy, and the ratio of LC3B short segment (LC3B-II) to LC3B long segment (LC3B-I) is representative of the level of autophagy [43]. Consistent with decreased mitophagy, there was also a significant decrease in the LC3B-II/LC3B-I ratio in aging versus young retinas, suggesting a decrease in overall autophagy levels (Figure 4D, E).…”
Section: Resultsmentioning
confidence: 99%
“…The decline in Pink1 expression was also observed in the nuclei and cytoplasm of the RGC layer of aging retinas [42] (Figure 4F). Microtubule-associated protein 1B light chain 3B (LC3B) is a marker of autophagy, and the ratio of LC3B short segment (LC3B-II) to LC3B long segment (LC3B-I) is representative of the level of autophagy [43]. Consistent with decreased mitophagy, there was also a significant decrease in the LC3B-II/LC3B-I ratio in aging versus young retinas, suggesting a decrease in overall autophagy levels (Figure 4D, E).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that overexpression of miR-146b in breast cancer cells downregulated epidermal growth factor receptor expression, inhibited invasion and migration in vitro , and suppressed experimental lung metastasis in vivo , 8 suggesting that miR-146b serves as a tumor suppressor. However, some studies reported that miR-146b might act as an oncogene to promote proliferation, migration, and invasion of colorectal and prostate cancers 9, 10. Despite the fact that surging studies of the biogenesis and mechanisms of miR-146b were involved in the pathogenesis of multiple tumors, the accurate expression level and mechanistic function of miR-146b in bladder cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are various cellular signalling pathways regulating autophagy, including mTOR, PTEN and AMPK (Zhou et al, 2013;Liu et al, 2018a;Tomas-Hernández et al, 2018). Among them, mTOR signaling pathway is the most important mechanism (Zhou et al, 2013;Gao et al, 2018;Liu et al, 2018b). Our results showed that MAN treatment decreased the expression levels of phosphorylated-AKT, -mTOR, and -S6 ( Figure 3G), demonstrating that AKT/mTOR pathway is responsible for MAN-triggered autophagy.…”
Section: Discussionmentioning
confidence: 70%